Two Loops Guide - Colchester, Joss (Si Network, 2023)
The Two Loop model is a nonlinear theory of change based upon the idea s of living systems created by Margaret Wheatley & Deborah Frieze. It provides us with insight into the simultaneous growth and decline proc ess that are underway within a system during a transition period. In t his way, it provides a heuristic for us to better try and recognize an d connect the past to the future during a change process. It likewise gives us the possibility to try and come to some consensus about where we might be as a group in this process of change and the best actions to take at different stages. This guide will be of relevance for anyo ne involved in a complex organizational change process.